EFFECT OF PRANAYAMA AND YOGASANAS ON LIPID PROFILE IN NORMAL HEALTHY VOLUNTEERS - Surendra, BV (International Journal of Clinical and Biomedical Research, 2016)
Background: The present study was conducted to assess the impact of Pranayama and Yogasanas on healthy individuals in Patanjali yoga centre, Kurnool. Methodology: 30 subjects in the age group of 25-35 years, of either sex were included in the study and none of them had a history of Lipid Metabolism Disorders. The scope and objectives of the present study were explained to the subjects and their written consent was obtained for participation in the study. The Institutional Ethical Committee had approved the study protocol and design. Pranayamas and yogasanas were practiced by the subjects for One and half hour on each day for three months. The Lipid profiles were compared one day prior and one day after experimental period. Result: A Significant reduction was observed in Total Triglycerides, Total Cholesterol, VLDL-cholesterol and LDL Cholesterol and a significant elevation of HDL-cholesterol was seen in the healthy volunteers at the end of 3 months. Conclusion: It was concluded from the results of the study that yoga practice has brought positive changes in the lipid profile in healthy individuals. The results of the present study indicate that Pranayama and yogasanas can be helpful in patients with lipid metabolism disorders Patients.